INTEGRAL HUMAN DEVELOPMENT (IHD) IN LEILA S. CHUDORI’S NOVEL LAUT BERCERITA: A LITERARY PSYCHOLOGICAL ANALYSIS - Hidayati Hidayati; M Manugeren; Purwarno Purwarno; Pardi Pardi; Mayasari Mayasari; Devi Pratiwy (English Review: Journal of English Education, 2025)
Integral Human Development cannot be separated from the lives of people as every human being is dynamic and is always developing both internally and externally. The study of integral development makes a major contribution to improving the quality of life for individuals and groups so that everyone can anticipate what needs to be done. The entire research is conducted using a qualitative descriptive research method with a discourse analysis approach and supported by Integral Human Development theories tied to psychology of literature with a thought that personality development is related to the existences of the characters in the novel and is a discussion point in psychology of literature. Integral Human Development (IHD) or Whole Human Development is a concept that emphasizes the development of humans as a whole covering physical, intellectual, emotional, social, and spiritual aspects so that humans can achieve a balance between personal growth and social contribution. The novel is chosen as the research object as the novel highlights talks much of the personality progress of the characters in fighting for their rights. Within the internal human development conceptual framework supported by the theory of psychology of literature, there are four steps to improve the quality of life, which become the subject of the research. The results of the analysis show that the novel provides an important lesson that success can be obtained through the implementation of Integral Human Development which in the novel is manifested in the forms of social awareness, hard work, tolerance, and discipline.